DAYA TERIMA PRODUK PASTA GIGI DARI LIMBAH KULIT PISANG - Nabila Novitasari; Nor Aini; Febriana Arianti; Irfany Rupiwardani (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2019)
Banana skin is a waste that is not utilized by the community. During this time banana plants usually require banana leaves for traditional food packaging. This is because people's knowledge is still minimal about processing banana skin even though the banana peel we usually dispose of every day contains organic and inorganic substances. The mineral content of vitamin C and fasfor in banana skin is very high. The purpose of this study was to find out the consumer acceptance of three toothpaste products. The non-parametric statistical method uses the Friedman Test and the determination of the best treatment uses the index of effectiveness. The results showed that the best combination of treatments on consumer acceptance of toothpaste in an organoleptic manner was obtained from the product market dental unit (Y) with a product value of 0.0,513 with the following characteristics: 28, and aroma 3.68